2020
DOI: 10.1007/s12671-020-01335-4
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Affect-Network Density: Does Mindfulness Facilitate Disengagement from Affective Experiences in Daily Life?

Abstract: Objectives Mindfulness has been positively associated with affective well-being, which may be explained by improved affective disengagement from prior experiences. Methods We used a dynamic network approach to represent temporal interconnections between specific affective states (i.e., network density)-with less interconnected states indicating better affective disengagement-to investigate whether mindfulness predicted a lower network density. One-hundred twenty-five undergraduate students (M age = 22.87; SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…It is essential to notice that initial mindfulness training involves applying psychological attitudes whilst relating to internal and external experiences primarily in the controlled context of the formal meditation exercise (Crane et al, 2017). Likely, incorporating mindfulness attitudes as coping strategies to deal with daily living activities and social relationships may require more extensive training (Jackson et al, 2019; Rowland & Wenzel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to notice that initial mindfulness training involves applying psychological attitudes whilst relating to internal and external experiences primarily in the controlled context of the formal meditation exercise (Crane et al, 2017). Likely, incorporating mindfulness attitudes as coping strategies to deal with daily living activities and social relationships may require more extensive training (Jackson et al, 2019; Rowland & Wenzel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness research has shown that the skill of acceptance may require more time and training to develop than other mindfulness components, such as mere observational or attentional skills (Baer et al, 2012 ; Desbordes et al, 2014 ). This may also explain why only individuals with prior mindfulness meditation experience (but not novices) seemed to be able to effectively detach from past emotions when being more mindful (Rowland & Wenzel, 2020 ). Thus, the benefits of SC (and mindfulness) on affective detachment may only unfold after significant training and internalization of the importance to fully accept the present moment experience.…”
Section: Discussionmentioning
confidence: 99%
“…Dashed gray lines indicate the true causal effect. mann et al, 2016;Rowland & Wenzel, 2020) typically ask participants the degree to which they current feel anxious multiple times a day, that is, at the moment they received the measurement prompt. In that situation, it is clear that the researchers aim to capture snapshot measurements of some time-varying psychological process.…”
Section: States and Traits In Psychological Measurementmentioning
confidence: 99%
“…Similar comparisons can be made with depressed mood, where experience sampling studies typically query depressed mood levels at the moment of measurement (e.g. Bringmann et al, 2016;Rowland & Wenzel, 2020); cross-sectional studies based on the Beck Depression Index or DSMcriteria ask participants to assess their depressed mood over the past week, two weeks or the past 30 days (e.g., Alegria et al, 2007;Beck et al, 1987;Fried et al, 2016;Kendler et al, 2018); while still other cross-sectional studies assess stable levels of depressed mood using measures designed to assess trait positive and negative affect (e.g., Clark & Watson, 1991;Watson, Clark, et al, 1994). This already gives some indication that the (perhaps implicit) measurement model being used by empirical researchers in cross-sectional settings may be closer to that of equilibrium measurements than that of snapshot measurements.…”
Section: States and Traits In Psychological Measurementmentioning
confidence: 99%